Optimization of Sample Preparation and Phloroglucinol Analysis of Marselan Grape Skin Proanthocyanidins using HPLC-DADESI- MS/MS - Liang, N.-N.; He, F.; Pan, Q.-H.; Wang, J.; Reeves, M.J.; Duan, C.-Q. (South African Journal of Enology and Viticulture, 2016)
Proanthocyanidins are a group of oligomeric or polymeric flavan-3-ols that are highly significant contributors to astringency in grapes and wines. An orthogonal L9(3)4 test was adopted to determine the optimal extraction conditions and acid-catalysis cleavage of proanthocyanidins in the presence of excess phloroglucinol. The qualitative and quantitative analyses were done using HPLC-DAD-ESI-MS/MS. The results showed that the maximum extraction was obtained using 0.3 mol/L of HCl and 0.005 g of ascorbic acid with incubation at 70°C for 20 min. The precision and accuracy of this method were acceptable. The composition of free flavan-3-ols and proanthocyanidins in the skins of ‘Marselan’ grapes (Vitis vinifera L. cv.) was investigated. (-)-Epigallocatechin was found to be the most abundant free flavan-3-ol monomer and terminal subunits, whereas the extension subunits were mainly (-)-epicatechin-3-O-gallate in the early developmental stages, and primarily (-)-epigallocatechin and (-)-epicatechin in the middle and late stages.